2012
DOI: 10.3389/fgene.2012.00009
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology of Observed Negative Emotionality from 14 to 24 Months

Abstract: We examined the magnitude of genetic and environmental influences on observed negative emotionality at age 14, 20, and 24 months. Participants were 403 same-sex twin pairs recruited from the Longitudinal Twin Study whose emotional responses to four different situations were coded by independent raters. Negative emotionality showed significant consistency across settings, and there was evidence of a latent underlying negative emotionality construct. Heritability decreased, and the magnitude of shared environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Some of the CADS items are not developmentally appropriate for toddlers. Also, although there is evidence for the reliability and validity of the antisocial propensity measures examined here (Rhee et al, 2012; Rhee, Boeldt, et al, 2013; Smith et al, 2012), they were chosen post-hoc rather than developed specifically to test the developmental propensity model, as the CADS was. Moreover, it was not possible to examine whether the very early antisocial propensity dimensions examined here and the CADS dimensions assess the same constructs, as the CADS was not available in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the CADS items are not developmentally appropriate for toddlers. Also, although there is evidence for the reliability and validity of the antisocial propensity measures examined here (Rhee et al, 2012; Rhee, Boeldt, et al, 2013; Smith et al, 2012), they were chosen post-hoc rather than developed specifically to test the developmental propensity model, as the CADS was. Moreover, it was not possible to examine whether the very early antisocial propensity dimensions examined here and the CADS dimensions assess the same constructs, as the CADS was not available in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, antisocial propensity dimensions examined included negative emotionality, behavioral inhibition (a construct that may be inversely associated with daring), concern and disregard for others (constructs closely related to prosociality), general cognitive ability, and language ability. These dimensions were chosen given the similarity of the constructs available to those discussed in the original model, and because the reliability and validity of these assessments in toddlerhood were established in previous studies (Rhee et al, 2012; Rhee, Boeldt, et al, 2013; Smith et al, 2012). …”
Section: Support For the Developmental Propensity Model And The Presementioning
confidence: 99%
“…To produce nationally representative statistical estimates and to attach correct standard errors to these estimates, we performed a survey-weighted analysis using weights provided by the Health and Retirement Study. (13, 14) The statistical analyses were performed using the statistical software Stata, version 10.1, and the statistical analysis software SAS, version 9.2.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Parent report of negative emotionality is moderately to highly heritable in infancy, toddlerhood, and middle childhood (generally 40%-70%), with the remaining variance typically explained by nonshared environment (Goldsmith, Lemery, Buss, & Campos, 1999;Goldsmith et al, 1997;Singh & Waldman, 2010;Tackett, Waldman, Van Hulle, & Lahey, 2011). Observational measures of broad negative emotion are rare in behavioral genetic studies, but one study finds a latent factor of observed anger and experimenter rated negativity to be heritable at 14 (65%) and 20 (40%) months, with shared environment at 20 (38%) and 24 (51%; Rhee et al, 2012) months. Heritability is similar for reported fear (56%-83%), anger (66%), and sadness (71%-75%; Emde, Robinson, Corley, Nikkari, & Zahn-Waxler, 2001;Goldsmith & Lemery, 2000;Mullineaux, Deater-Deckard, Petrill, Thompson, & DeThorne, 2009), and infants' anger and fear show substantial, largely independent genetic variance (Goldsmith et al, 1999).…”
Section: Heritability Of Temperamentmentioning
confidence: 99%